Excitatory Amino acid transporter expression in the essential tremor dentate nucleus and cerebellar cortex: A postmortem study. (November 2016) - Wang, Jie; Kelly, Geoffrey C.; Tate, William J.; Li, Yong-Shi; Lee, Michelle; Gutierrez, Jesus; Louis, Elan D.; Faust, Phyllis L.; Kuo, Sheng-Han
Abstract: Background: Genome-wide association studies have revealed a link between essential tremor (ET) and the gene SLC1A2, which encodes excitatory amino acid transporter type 2 (EAAT2). We explored EAAT biology in ET by quantifying EAAT2 and EAAT1 levels in the cerebellar dentate nucleus, and expanded our prior analysis of EAAT2 levels in the cerebellar cortex. Objective: To quantify EAAT2 and EAAT1 levels in the cerebellar dentate nucleus and cerebellar cortex of ET cases vs . controls. Methods: We used immunohistochemistry to quantify EAAT2 and EAAT1 levels in the dentate nucleus of a discovery cohort of 16 ET cases and 16 controls. Furthermore, we quantified EAAT2 levels in the dentate nucleus in a replicate cohort (61 ET cases, 25 controls). Cortical EAAT2 levels in all 77 ET cases and 41 controls were quantified. Results: In the discovery cohort, dentate EAAT2 levels were 1.5-fold higher in 16 ET cases vs. 16 controls (p = 0.007), but EAAT1 levels did not differ significantly (p = 0.279). Dentate EAAT2 levels were 1.3-fold higher in 61 ET cases vs. 25 controls in the replicate cohort (p = 0.022). Cerebellar cortical EAAT2 levels were 20% and 40% lower in ET cases vs. controls in the discovery and the replicate cohorts (respective p values = 0.045 and < 0.001). Conclusion: EAAT2 expression is enhanced in the ET dentate nucleus, in contrast to differentially reduced EAAT2 levels in the ET cerebellar cortex, which might reflect a compensatory mechanism to maintain excitation-inhibition balance in cerebellar nuclei. Highlights: EAAT2 levels are decreased in the essential tremor (ET) dentate nucleus. The decrease in EAAT2 levels in the ET dentate nucleus is not due to gliosis. Decreased EAAT2 levels in ET dentate nucleus are replicated in a large cohort. In contrast, EAAT2 levels are increased in the cerebellar cortex of ET cases. Dysregulated EAAT2 levels in cerebellum might contribute to tremor.